KONTEKSTUALISASI PENGELOLAAN ZAKAT UNTUK UMAT - Aden Rosadi (Asy-Syari'ah, 2015)
This paper describes the urgency of the meaning of zakat in the welfare of the peoples. The existence of charity is not only for the individual normative duty, but also contains a social meaning in the context of collective responsibility that involving some subjects such as muzakki, amyl, mustahik, and government. In practical terms, the obligation of zakat management in a professional manner, at least must be supported by three aspects, namely the aspect of substance, structure, and culture.